(untitled) (Journal of Medical Sciences, 2018)
Heterotaxy syndrome is a rare complex syndrome characterized by cardiac and extra cardiac congenital malformations. The syndrome is divided into two main groups; right isomerism (Ivemark syndrome, asplenia) and left isomerism (polysplenia syndrome). We report a polysplenia syndrome with agenesis of head and uncinate process of the pancreas in a 30-year-old woman who was admitted to our clinic with complaints of loin pain and dysuria.